Synthèse d’entretien avec madame la juge des enfants au tribunal de grande instance de Ouagadougou - Tapsoba, Tatiana Nadine (Criminal justice institutions and the social trajectories of adolescents/youth in Burkina Faso: endogenous/local forms and patterns of punishment, 2021)
The interviewee for this interview summary was the children's judge at the Ouagadougou high court. The interviewees discussed misconduct in general, and children's misconduct in particular, as well as the process of dealing with it, the mechanisms for dealing with misconduct, the forms and actors of mediation, the population's perception of modern and traditional justice, and collaboration between these two bodies...
Keywords: Administration of Justice; Teenagers; Youth; Punishment; Children; Court